How can European regulation on ESG impact business globally? - Rocío Redondo Alamillos; Frédéric Rozeira de Mariz (Journal of Risk and Financial Management, 2022)
The European Union (EU) has impacted regulation worldwide in areas ranging from data protection to trade or antitrust. In select fields, it has defined stringent standards and has had an impact on global business because of the size of its market and the price of participating in it. The purpose of this paper is to analyze the main provisions of the EU regulation on Environmental, Social, and Governance (ESG) and determine whether and how it will have an impact on business globally, including regulations around disclosure for companies, taxonomy for the asset management sector, supply chain due diligence requirements, new mechanisms such as carbon markets, or non-tariffs restrictions on international trade. For this, our analysis includes an in-depth review of the literature on EU regulation of the past 20 years, complemented with interviews with experts in the field, in order to understand the main tools used by European policymakers in ESG regulations to understand their effect. The analysis adds to the body of research pertaining to the impact of regulation on business and the growing body of research on sustainable finance. We find that the new ESG regulation impacts countries outside of the EU, influencing regulation worldwide, and raising the question of possible regulatory arbitrage.
Keywords: 650; Europe; Brussels Effect; ESG; ESG Brussels Effect; regulation; regulatory arbitrage; sustainable finance